A BODIPY-Tagged Phosphono Peptide as Activity-Based Probe for Human Leukocyte Elastase - Schulz-Fincke, Anna-Christina; Blaut, Michael; Braune, Annett; Gütschow, Michael (ACS medicinal chemistry letters, 2018)
Human leukocyte elastase plays a crucial role in a variety of inflammatory disorders and represents an important subject of biomedical studies. The chemotype of peptidic phosphonates was employed for the design of a new activity-based probe for human leukocyte elastase. Its structure combines the phosphonate warhead with an adequate peptide portion and a BODIPY fluorophore with a clickable ethinylphenyl moiety at meso position. The probe 6 was assembled by copper-catalyzed alkyne–azide 1,3-dipolar cycloaddition. It was characterized as an active site-directed elastase inhibitor exhibiting a second-order rate constant of inactivation of 88400 M–1s–1. The suitability of 6 as a fluorescent probe for human leukocyte elastase was demonstrated by in-gel fluorescence analysis. Labeling experiments and inhibition data toward a panel of related proteases underlined the selectivity of the probe for the targeted leukocyte elastase.